Mapping the hand, foot and face representations in the primary motor cortex — Retest reliability of neuronavigated TMS versus functional MRI - Weiss, Carolin; Nettekoven, Charlotte; Rehme, Anne K.; Neuschmelting, Volker; Eisenbeis, Andrea; Goldbrunner, Roland; Grefkes, Christian (NeuroImage (Orlando, Fla.), 2013)
Functional magnetic resonance imaging (fMRI) is a frequently used non-invasive mapping technique for investigating the human motor system. Recently, neuronavigated transcranial magnetic stimulation (nTMS) has been established as an alternative approach. We here compared the test–retest reliability of both mapping techniques with regard to the cortical representations of the hand, leg, face and tongue areas. Ten healthy subjects were examined three times (intervals: 3–5days/21–35days) with fMRI and nTMS. Motor-evoked potentials were recorded from the abductor pollicis brevis, plantaris, mentalis and the tongue muscles. The same muscles were activated in an fMRI motor task. Euclidean distances (ED) between hotspots and centers of gravity (CoG) were computed for the respective somatotopic representations. Furthermore, spatial reliability was tested by intersession overlap volumes (OV) and voxel-wise intraclass correlations (ICC). Feasibility of fMRI was 100% for all body parts and sessions. In contrast, nTMS was feasible in all sessions and subjects only for the hand area, while mappings of the foot (90%), face (70%) and tongue representations (40%) remained incomplete in several subjects due to technical constraints and co-stimulation artifacts. On average, the mean ED of the hotspots was better for fMRI (6.2±1.1mm) compared to nTMS (10.8±1.9mm) while stability of CoG was similar for both methods. Peak voxel reliability (ICC) was high for both methods (>0.8), and there was no influence of inter-session intervals. In contrast, the reliability of mapping the spatial extent of the hand, foot, lips and tongue representations was poor to moderate for both fMRI and nTMS (OVs and ICC<50%). Especially nTMS mappings of the face and tongue areas yielded poor reliability estimates. Both methods are highly reliable when mapping the core region of a given target muscle, especially for the hand representation area. In contrast, mapping the spatial extent of a cortical representation area was only little reliable for both nTMS and fMRI. In summary, fMRI was better suited when mapping motor representations of the head, while nTMS showed equal reliability for mapping the hand and foot representation areas. Hence, both methods may well complement each other. [Display omitted] ► Test–retest reliability of M1 mapping by nTMS and fMRI compared in the same cohort ► Centers of gravity of nTMS and fMRI equally well reliable (5–8mm deviation) ► NTMS centers of gravity better reliable than nTMS hotspots ► Mapping the lips and the tongue area with nTMS hampered by direct stimulation effects ► Motor representations of the lips and tongue more reliable when mapped with fMRI